Treatment of renal manifestations of ANCA-associated vasculitis - Kresimir Galesic; Danica Ljubanovic; Ivica Horvatic (Society of Diabetic Nephropathy Prevention, 2013)
Context: Vasculitis is a clinicopathological entity characterized by inflammation and necrosis of blood vessels. Evidence Acquisitions: Directory of Open Access Journals (DOAJ), Google Scholar, Pubmed (NLM), LISTA (EBSCO) and Web of Science have been searched. Results: Two major autoantigens for ANCA are myeloperoxidase (MPO) and proteinase 3 (PR3), which are proteins in the primary granules of neutrophils and in the lysosomes of monocytes. They are expressed in mature neutrophils of patients with ANCA, while absent in healthy subjects. Conclusions: The kidney is the most commonly affected vital organ in ANCA-associated vasculitis, and patient outcomes are largely determined by the severity of renal disease at diagnosis and by its response to treatment.